Marine diatoms from Buenos Aires coastal waters (Argentina). II. Thalassionemataceae and Rhaphoneidaceae - Sar, Eugenia A. (2007)
This study describes the diversity of the species belonging to the diatom families Thalassionemataceae Round and Rhaphoneidaceae Forti frequently found in the temperate marine coastal waters of Buenos Aires Province, Argentina, from October 1994 to September 2000. It comprises morphological, taxonomic and distributional analysis of species found in planktonic samples collected at San Clemente del Tuyú, Santa Teresita, La Lucila del Mar, Mar de Ajó, Nueva Atlantis, Pinamar and Villa Gesell. Raw and cleaned samples were analysed with light and scanning electron microscopy. Four taxa of the genus Thalassionema Grunow ex Mereschkowsky amend. Hallegraeff, one of the genus Lioloma Hasle, two of the genus Delphineis Andrews and one of the genus Rhaphoneis Ehrenberg, were identified. Thalassionema pseudonitzschioides (Schuette & Schrader) Hasle, Thalassionema synedriforme (Greville) Hasle and Lioloma pacificum (Cupp) Hasle in Hasle & Syvertsen are new records for Argentina.